Village Governance in Realizing Excellent Service in Jumantuang Village, Siempat Nempu District, Dairi Regency - Julia Ivanna (JPAS (Journal of Public Administration Studies), 2022)
This study aims to determine Village Governance in Realizing Excellent Service in Jumantuang Village, Siempat Nempu District, Dairi Regency. Its governance is one part of realizing excellent service provided by village government officials. The research method used by researchers is descriptive qualitative research methods. Data collection tools used were observation and interviews and documentation. The data analysis technique used was qualitative data analysis techniques. This technique functions to process qualitative data and analyze data that has been obtained from the results of observations and interviews related to village governance in realizing excellent service. Narrative data obtained from interviews and observations are interpreted for further analysis. So in qualitative research, data analysis must start from the beginning. The results showed that its governance in realizing excellent service in Jumantuang Village has gone well. Jumantuang Village, as a public servant has served the community well and refers to the four characteristics of excellent service, namely by providing easy and fast, open services, in accordance with what the community needs, and implementing a familiarity with the community in Jumantuang Village. So that, the service in the community can be said to be better than before. The hope is that the government and the community can establish good cooperation in the success of service activities within Jumantuang Village.